Strategi Pembelajaran Guru Aqidah Akhlak Dalam Menanamkan Sikap Sosial di SDS IT Al-Hakim - Indryani, Ainun Jannah; Arlina; Berampu, Wantri Anggraini; Syahputri, Nurtika; Tasya, Defina (Ikatan Dai Indonesia, 2023)
This study aims to describe what strategies are used by Aqidah Akhlak teachers at SDS IT Al-Hakim Tembung in instilling social attitudes. The research methodology used in this study is a qualitative approach which provides a comprehensive and complex picture presented in the form of words and primary data processed from informants with data collection techniques in the form of interviews, direct observation and observation. The results of the study were in the form of information about the role of the Aqidah Akhlak teacher in instilling social attitudes of students and the various learning strategies used by Ms. Annisa Putri as the Aqidah Akhlak teacher in Aqidah Akhlak learning in the context of fostering social attitudes of students at SDS IT Al-Hakim Tembung.